Pengembangan bahan ajar menulis naskah drama bermuatan kearifan lokal dan pendidikan karakter - Nia Ulfa Martha; Dyah Wijayawati; Vera Krisnawati; Bivit Anggoro Prasetyo Nugroho (JINoP (Jurnal Inovasi Pembelajaran), 2022)
Students have difficulty in writing drama scripts. Teachers Indonesian are required to be able to develop teaching materials as a source of material information that is important for students to be skilled in writing drama scripts. Teaching materials developed by teachers should be charged with local wisdom and character education. This research aims to realize the learning materials of writing drama scripts loaded with local wisdom and character education. This research uses Research and Development (R&D) approach from Borg and Gall which is tailored to the needs of this research. This research and development resulted in teaching material writing drama scripts loaded with local wisdom and character education. As a learning material to write a drama script, the material contains six main parts: writing a drama script, intrinsic elements of drama, character education values, examples of local wisdom, examples of drama scripts that are charged with local wisdom and character education, and evaluations to measure students' competence. The procedure is divided into seven main stages, namely theoretical and practical analysis, analysis of the needs of students and teachers, prototyping, material expert tests, prototype revisions, product use tests, and product development of thinking-pair-sharing techniques writing drama scripts